Landscape, memory and history : anthropological perspectives - Stewart, Pamela J.; Strathern, Andrew (Pluto Press, 2003)
"How do people perceive the land around them, and how is that perception changed by history? This book explores this question from an anthropological angle, assessing the connections between place, space, identity, nationalism, history and memory in a variety of different settings around the world. Taking historical change and memory as key themes, it is a broad study that will appeal to a readership across the social sciences. Contributors from North America, Australia, New Zealand, Taiwan, and Europe explore a wide variety of case studies that includes seascapes in Jamaica; the Solomon Islands; the forests of Madagascar; Aboriginal and European notions of landscape in Australia; place and identity in 19th century maps and the bogs of Ireland; contemporary concerns over changing landscapes in Papua New Guinea; and representations of landscape and history in the poetry of the Scottish Borders."-- Provided by publisher
Keywords: Landscape assessment.; Landscape changes.; Landscapes -- Social aspects.; Geographical perception.; Paysages -- Évaluation.; Paysages -- Modifications.; Paysages -- Aspect social.; Perception géographique.; Miriwoong -- Miriuwung people (K29) (WA SD52-14); Gajerrong -- Gajirrawoong people (K37.1) (WA SD52-15); Koko Bera people (Y85) (Qld SD54-15); East Kimberley area (North NT SD52-15); East Kimberley area (WA SD52, SE52); Cape York Peninsula (Qld SC54, SD54, SD55); Trubanamen (Qld NW Cape York SD54-15); Native title -- Agreements -- Indigenous Land Use.; Demography -- Population mobility.; Economic sectors -- Agriculture and horticulture.; Race relations -- Violent.; Indigenous peoples -- Pacific.; 73.99 ethnology: other.; SOCIAL SCIENCE -- Human Geography.; SOCIAL SCIENCE -- Anthropology -- Cultural.; Geographical perception; Landscape assessment; Landscape changes; Landscapes -- Social aspects; Anthropologie; Landschaft; Ethnische Identität; Anthropogeografie; Landschappen.; Antropologische aspecten.; landschap; landscape; fysiografische elementen; physiographic features; perceptie; perception; verandering; change; antropologie; anthropology; geschiedenis; history; omgevingspsychologie; environmental psychology; Land Evaluation; Environmental Psychology; Landevaluatie; Omgevingspsychologie; Aufsatzsammlung.